CREATION OF PRODUCT PHOTOGRAPHY AS VISUAL MARKETING ASSETS FOR THE MIRELLE 3 BRIGHTENING KIT - Wicaksono, Dicky Wahyu; Murtiyoso, Onang (LPPM Univ. Ibn Khaldun Bogor, 2025)
The skincare sector in Indonesia has undergone swift expansion, leading to heightened rivalry. In digital marketing, product photography serves as a crucial visual representation that profoundly affects consumer perception and purchase choices. This project seeks to provide effective and uniform graphic assets for product photography to enhance the advertising of the Mirelle 3 Brightening Kit on digital channels. The design thinking technique was utilized, consisting of five stages: empathize, define, ideate, prototype, and test. The result of this project is a collection of high-key minimalist product shots that exude a clean, elegant, and professional appearance. This visual concept was intentionally selected to emphasize product distinctiveness, uphold brand identity consistency, and guarantee adaptability across diverse promotional mediums. The conclusion derived from this production process is that a user-centered strategy, informed by contemporary visual trends, may produce assets that boost visual appeal and bolster brand competitiveness in the digital marketplace. The final outputs have been implemented on the Shopee e-commerce platform and the brand's Instagram account.